Biogeoquímica de solos de manguezal do rio Jaguaribe (Brasil - CE) em resposta a bioturbação por caranguejos - Araújo Júnior, José Moacir de Carvalho (2010)
Mangroves are tropical coastal ecosystems with high biodiversity, consisting of trees and shrubs with high tolerance to salt, and animals typically residents of those regions. Among these, crabs demonstrate a great ecological and economic importance. These crustaceans have a high population density and high activity of soil mobilization, mainly due to the formation of burrows, which provide oxygenation and soil drainage, changing the dynamics of minerals in the vertical profile. Likewise, climate changes and seasonal marked variations of rainfall regime, as occurring in the semi-arid areas, can cause oxidation of pyrite due to replacement of the water in the soil for oxygen gas during the dry season, with a consequent increase in release fraction of iron associated with it. In our study, the analysis of physical-chemical standards and concentrations of active iron and pyritic iron in soils under the action of mangrove crab (Ucides cordatus), comparing the values found between the rainy and dry seasons, and between this area with another area under the activity of the crab specie Uca maracoani. We found significant variations in the geochemical forms of Fe in soils of the area with U. cordadus between the dry and rainy seasons, as well when it was compared to the area with U. maracoani. The results demonstrate the distinct effects of seasonal variation and representatives of the fauna on the biogeochemistry of iron in the mangroves of the semi-arid region, highlighting the need for further studies in these areas in order to make future comparisons.